2021
DOI: 10.1021/acs.estlett.1c00217
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Forms of Mercury in Blue Marlin Billfish: Implications for Human Exposure

Abstract: resolution X-ray absorption near edge structure spectroscopy, we show that blue marlin (Makaira sp.), a common top predator consumed by humans, contains elevated concentrations of inorganic Hg(II) complexed as 57 ± 10% Hg-tetraselenolate (Hg(Sec) 4 ) and 43 ± 10% tiemannite (HgSe).The stable Hg-Se bond likely attenuates the bioavailability of Hg and counteracts some of its health hazards to consumers. Thus, monitoring the concentration of MeHg, rather than total Hg, in top predators such as marlin would provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…One liver tissue of an adult pilot whale from the Li et al data is an outlier with δ 202 Hg = 0.33‰ for f (MeHg) = 0.08 (black arrow in Figure a). Importantly, the hockey stick shape of the δ 202 Hg t versus f (MeHg) plots (Figure ) suggests the occurrence of an intermediate species in the MeHg → HgSe reaction, which was previously documented to be Hg­(Sec) 4 . The analysis here supports that Hg­(Sec) 4 is highly enriched in lighter Hg isotopes compared to MeHg, consistent with the observed MDF of mercury due to the demethylation of MeHg to Hg­(Sec) 4 , and to a lesser extent HgSe.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…One liver tissue of an adult pilot whale from the Li et al data is an outlier with δ 202 Hg = 0.33‰ for f (MeHg) = 0.08 (black arrow in Figure a). Importantly, the hockey stick shape of the δ 202 Hg t versus f (MeHg) plots (Figure ) suggests the occurrence of an intermediate species in the MeHg → HgSe reaction, which was previously documented to be Hg­(Sec) 4 . The analysis here supports that Hg­(Sec) 4 is highly enriched in lighter Hg isotopes compared to MeHg, consistent with the observed MDF of mercury due to the demethylation of MeHg to Hg­(Sec) 4 , and to a lesser extent HgSe.…”
Section: Resultssupporting
confidence: 84%
“…The enrichment of the biosphere in anthropogenic mercury (Hg) impacts wildlife and humans across the globe. Despite detailed understanding of the environmental conditions that promote the uptake of neurotoxic methylmercury (MeHg) in food webs, key knowledge gaps remain on the internal transformations, redistribution, and toxicologic mechanisms of Hg in higher organisms. Recently, advancement in the application of high energy-resolution X-ray absorption (HR-XANES) spectroscopy in wildlife identified that MeHg is detoxified to nontoxic mercury selenide (HgSe) through an intermediary Hg-tetraselenolate (Hg­(Sec) 4 ) species. The stepwise transformation of MeHg observed in bird and fish tissues (MeHg → Hg­(Sec) 4 → HgSe), likely initiated by selenoprotein P (SelP), provided the first in vivo mechanistic information for the observation of HgSe in the liver and extrahepatic tissues of marine mammals and seabirds using standard resolution X-ray absorption spectroscopy and electron microscopy. Although these two techniques provide critical structural information on mercury, they provide limited insight into biochemical processes essential for understanding the toxicokinetics of toxic MeHg in organisms (i.e., fate, tissue-specific exchange).…”
Section: Introductionmentioning
confidence: 99%
“… 55 , 85 Recent studies identified the intermediary Hg compound as Hg(Sec) 4 in a range of wildlife. 55 , 86 , 87 Assuming Hg(Sec) 4 is also the major intermediate demethylation product in marine mammals and using the Hg isotope measurements of HgSe particles and total Hg, 70 , 73 Manceau et al (2021) 71 applied a three endmember mixing model (i.e., δ 202 Hg MeHg , δ 202 Hg HgSe , and δ 202 Hg Hg(Sec)4 ) to estimate the chemical composition of Hg in pilot whale tissues. The results support that both the MeHg → Hg(Sec) 4 demethylation and the Hg(Sec) 4 → HgSe biomineralization processes are pronounced in the liver, while the demethylation process dominates in other tissues ( Figure 1 b).…”
Section: Mercury Isotope Dynamics In Biotamentioning
confidence: 99%
“…The potential methylation of iHg and demethylation of MeHg and the main locations for these processes in fish are still under debate. 87 , 114 117 …”
Section: Mercury Isotope Dynamics In Biotamentioning
confidence: 99%
“…The existing literature of Hg biocomplexes characterization in aquatic microorganisms is limited in terms of molecular mass spectrometry characterization. Using X-ray absorption spectroscopy high energy resolution fluorescence detected X-ray absorption near edge structure (XAS-HERFD-XANES or HR-XANES), several Hg species were identified inside biological cells, but also, X-ray absorption spectroscopy fine structure (EXAFS) can be used to elucidate the structural characterization of thiol functional groups among others (O/N) binding Hg. , …”
Section: Introductionmentioning
confidence: 99%